Middle/late Miocene hoplocetine sperm whale remains (Odontoceti: Physeteridae) of North Germany with an emended classification of the Hoplocetinae - Hampe, O. (Fossil Record, 2006)
Hoplocetus ritzi n. sp. is a new hoplocetine physeterid from the Bolboforma fragori /subfragoris Zone of the middle/late Miocene mica-clay of Groß Pampau in Schleswig-Holstein, North Germany. The Hoplocetinae are known from the early Miocene to the Pliocene. Comparative studies of cranial characters and tooth morphology allow an emended diagnosis of the Hoplocetinae Cabrera, 1926. Four genera, Diaphorocetus, Idiorophus, Scaldicetus, and Hoplocetus are included in this subfamily. The pattern of functional tooth wear deduced from the described Hoplocetus ritzi n. sp. remains is reminescent of that known from Orcinus orca. The hoplocetine physeterids possibly occupied the killer whale niche before the killer whales appeared during the middle Pliocene. Mit Hoplocetusritzi n. sp. wird ein neuer hoplocetiner Physeteride beschrieben. Der Fund stammt aus der Bolboformafragori /subfragoris Zone des mittel-/obermiozänen Glimmertons von Groß Pampau in Schleswig-Holstein, Norddeutschland. Die Hoplocetinae sind vom unteren Miozän bis ins Pliozän nachgewiesen. Anhand vergleichender Untersuchungen an wenigen Schädelmerkmalen und der Zahnmorphologie gelingt eine Neudiagnose der Hoplocetinae Cabrera, 1926 und eine vorläufige Abgrenzung zwischen den als valid angesehenen Gattungen dieser Unterfamilie, Diaphorocetus, Idiorophus, Scaldicetus und Hoplocetus. Das Abkauungsmuster der Zähne von Hoplocetusritzi n. sp. erinnert an das des heutigen Orcinusorca. Möglicherweise sind die hoplocetinen Pottwale habituell den Schwertwalen, die erdgeschichtlich erstmals im mittleren Pliozän auftreten, vergleichbar. doi:10.1002/mmng.200600002